2013
DOI: 10.1068/c11158
|View full text |Cite
|
Sign up to set email alerts
|

The Hurdles of Local Governments with Ppp Contracts in the Waste Sector

Abstract: Abstract:This paper identifies a number of the theoretical principles that apply to PPP contracts, introducing new case studies and policy discussions relevant for Europe and elsewhere.It discusses to what extent these contracts can and should be applied in the waste sector and performs a comparison between the purely contractual and the institutionalised models of PPP arrangements. We analyse four case studies in the 'wholesale' waste market in Portugal and examine the implementation and degree of success of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…chapters 4 and 6) so as to achieve satisfactory outcomes that are best-for-project (cf. cruz & Marques, 2013;da cruz et al, 2013;Sakal, 2005). 103 it is argued that, because of the inherent uncertainty and unpredictability of events in projects, PPP contracts are incomplete by definition.…”
Section: Public-private Boundaries In Implementationmentioning
confidence: 99%
“…chapters 4 and 6) so as to achieve satisfactory outcomes that are best-for-project (cf. cruz & Marques, 2013;da cruz et al, 2013;Sakal, 2005). 103 it is argued that, because of the inherent uncertainty and unpredictability of events in projects, PPP contracts are incomplete by definition.…”
Section: Public-private Boundaries In Implementationmentioning
confidence: 99%
“…According to a 2008 Skumatz Economic Research Associates survey of 700 North American municipalities, 29% of municipalities reported having public waste collection, 43% reported organized systems where services are contracted out to the private sector, and 23% reported fully privatized "open" waste and recycling collection systems [12]. Even in the European Union, waste collection is "organized" under different public-private partnership (PPP) arrangements [5]. The Twin Cities case study therefore illustrates a range of possible ways that the private sector can be involved in delivering municipal services and the implications that this range of involvement has on urban sustainability initiatives.…”
Section: Case Study and Methods: Organic Waste Recycling In The Twin mentioning
confidence: 99%
“…City governments can collaborate with the private sector to share the knowledge and resources needed to coordinate infrastructure investments through Public-Private Partnerships (P3s), for example, or household communications through joint advisory boards. When services are provided by the private sector through local government contracts, public officials can help advance policy aims by ensuring that these contracts are effectively managed and risk is properly allocated [5,32].…”
Section: Finding #3: Availability Of Policy Tools For Urban Sustainabmentioning
confidence: 99%
See 2 more Smart Citations